Research and critical Study of Muslim ruling periods in Andulus - Khan, Muhammad Anees; Irfan ullah, (Journal of Islamic and Religious Studies, 2017)
The golden Islamic history cannot be completed without the mention of Spain which was a bright star. It became one of the great Muslim civilizations; reaching its summit with the Umayyad caliphate of the tenth century. The heartland of Muslim rule was Southern Spain or Andulus. Different eras of Muslim rule in Andulus have been described in this research with an aim to highlight their apex and glory they achieved and then a focus on the reasons of their downfall as well. A brief introduction of the rulers in all eras with their major achievements and immersion in evil habits that led to their downfall has been the prime focus of this research. It gives us various glimpses from the course of history to reflect upon Muslim rule in Spain from a new perspective.